STRATEGI MEMPERCEPAT PEMBANGUNAN DESA MANDIRI: STUDI DI DESA KEMADANG, GUNUNGKIDUL - Kusumastuti, Nugrahani; Nur Arifah, Mir’atun (Universitas Islam Negeri Sunan Kalijaga, 2018)
The commitment of the government in developing villages has been implemented in ‘Nawacita Programs’, the theme of Developing Indonesia’s rural areas. For that, the developing country very impossible can regularly, if the government not prepared for this program with the excellently. Hence, this research is the goals for knowing of the strategy which doing of government in the implementation of developing transformation until making Kemadang Village become an independent rural area in 2015 old. In addition, this paper aims to explain about developing transformation form become in Kemadang Village who has an independent rural area. The result of the research shows to us that in the strategy of implementing, is the government of Village Kemadang conducted mapping potential area, coaching and mentoring, building of the network, and implemented of governance village become modern organizations. Meanwhile, the form of developing transformation is increasing of services, and health facilities. For the production of livelihood, society is increasingly in disaster mitigation.[Komitmen pemerintahan dalam membangun desa tertuang dalam Nawacita, yakni “Membangun Indonesia Dari Pinggiran Dengan Memperkuat Daerah-Daerah dan Desa dalam Kerangka Negara Kesatuan”. Sebuah pembangunan suatu daerah tidak akan terlepas dari campur tangan pemerintah itu sendiri. Oleh karena itu, penelitian ini bertujuan untuk mengetahui strategi yang dilakukan pemerintah dalam melaksanakan transformasi pembangunan hingga menjadikan Desa Kemadang menjadi desa mandiri pada tahun 2015. Selain itu, kajian ini hendak menjelaskan bentuk transformasi pembangunan yang terjadi di Desa Kemadang setelah menjadi desa mandiri. Hasil penelitian ini menunjukkan bahwa dalam hal strategi yang dilakukan, pemerintah Desa Kemdang melakukan pemetaan potensi, pembinaan dan pendampingan, membangun sinergisitas dan menerapkan tata kelola desa menjadi organisasi modern. Sedangkan wujud dari transformasi pembangunan itu sendiri ialah terjadi peningkatan pada pelayanan, sarana dan prasarana kesehatan. Dalam keragaman produksi masyarakat dan program dalam hal mitigasi bencana juga turut meningkat.]